Intravenous immunoglobulin in isoimmune haemolytic disease of newborn: an updated systematic review and meta-analysis. Issue 4 (10th February 2014) - Louis, Deepak; More, Kiran; Oberoi, Sapna; Shah, Prakesh S
Abstract : Background: Intravenous immunoglobulin (IVIg) is used in neonates with isoimmune haemolytic disease to prevent exchange transfusion (ET). However, studies supporting IVIg had methodological issues. Objective: To update the systematic review of efficacy and safety of IVIg in neonates with isoimmune haemolytic disease. Methods: MEDLINE, Embase databases and Cochrane Central Register of Controlled Trials (Cochrane Library) were searched (from inception to May 2013) for randomised or quasi-randomised controlled trials comparing IVIg with placebo/controls in neonates with isoimmune haemolytic disease without any language restriction. Three investigators assessed methodological quality of included trials. Meta-analyses were performed using random effect model and risk ratio (RR)/risk difference (RD) and mean difference with 95% CI calculated. Main results: Twelve studies were included, ten trials (n=463) of Rh isoimmunisation and five trials (n=350) of ABO isoimmunisation (three studies had both population). Significant variations in risk of bias precluded an overall meta-analysis of Rh isoimmunisation. Studies with high risk of bias showed that IVIg reduced the rate of ET in Rh isoimmunisation (RR 0.23, 95% CI 0.13 to 0.40), whereas studies with low risk of bias that also used prophylactic phototherapy did not show statistically significant difference (RR 0.82, 95% CI 0.53 to 1.26). For ABO isoimmunisation, only studies with high risk of bias were available and meta-analysis revealed efficacy of IVIg in reducing ET (RR 0.31, 95% CI 0.18 to 0.55). Conclusions: Efficacy of IVIg is not conclusive in Rh haemolytic disease of newborn with studies with low risk of bias indicating no benefit and studies with high risk of bias suggesting benefit. Role of IVIg in ABO disease is not clear as studies that showed a benefit had high risk of bias.